Contemplating Toxicity of Atrazine on Lipid Profile of Fresh Water Fish (Ctenopharyngodono idella): An Experimental Approach: Toxicological effects of pollutants on aquatic fauna - Khan, Ahsan; Shah, Nazish; Alam, Mukhtar; Rahman, Khaliq Ur (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Productivity of agriculture is dependent upon the utilization of herbicides but they find avenues to get into water bodies, affecting aquatic fauna, particularly fish. The current effort accordingly focused to contemplate toxicity of sub lethal concentration of herbicide i.e. atrazine by estimating the lipid profile that included Cholesterol (CH), Triglyceride (TG), High density lipid (HDL) and Low density lipid (LDL) of freshwater grass carp, (Ctenopharyngodon idella) for (24, 48, 72, 96, 240, 360 and 600 hrs) under the dose (15, 13, 10, 08, 06, 04 and 02 μl L-1) respectively. Merck micro lab 300 biochemistry analyzer was used for analyzing lipid profile. Acute toxicity exposure explored that all components of total lipids documented decline in concentration against each time period and maximum decrease was observed against 72h exposure respectively. Similarly chronic toxicity exposure also indicated the decline against each time period and maximum decline in CH, TG and LDL was observed against 600h while HDL showed reduction in concentration against 360h exposure respectively. In all component of the lipid profile, significant decline in concentration was observed as; P<0.05, P ≤ 0. 01 and P ≤ 0. 001, specifically in acute toxicity groups as compared to chronic toxicity groups thus showing undesirable effects of on aquatic fauna present inside water bodies